The Effectiveness of Expressive Writing Guidance Technique on the Expression of Emotion and Stress of State Junior Hight School - Irda, Ulya Sofia; Wangid, Muhammad Nur (Journal of Educational Sciences, 2025)
Inconsistency of findings regarding the effectiveness of expressive writing guidance techniques on emotional and stress expression. This study aims to determine the effectiveness between the expression of emotion and stress of students who get expressive writing guidance compared to discussion techniques. The research method used is an experiment, with the type of true experiment design. Involving 64 students from grade 9 of State Junior High School, 3 Depok were divided into two experimental groups (n= 32) and control groups (n= 32) through a cluster sampling. This study was conducted in three stages: pretest, treatment and posttest posttest. Construct validity fit model category. The reliability of scale was tested using Cronbach's Alpha, and a coefficient of emotional expression of 0.872 and stress of 0.833 was obtained, indicating that the level of reliability high category. Data collection techniques using the emotional expression scale and stress scale. The data analysis technique used is the MANOVA. The test results showed that the treatment simultaneously affected emotional expression and stress with Wilks' Lambda = 0.001, p < 0.05. Therefore, guidance techniques for expressive writing effectively express emotions and stress in State Junior High School 3 Depok students.